AGROECOSYSTEMS SUSTAINABILITY OF CASSAVA PRODUCTION OF PARAÍBA RURAL AREA FROM THE PERSPECTIVE OF BIOGRAM - Valdenildo Pedro da Silva; Ranielle Freire da Silva; Anieres Barbosa da Silva; Leci Martins Menezes Reis (Redes, 2015)
Agriculture modernization resulting from green revolution occurred through means of diverse technological innovations as soluble fertilizers, pesticides, agricultural machinery and genetically modified seeds, aimed at increasing food production. However, the indiscriminate use of these innovations by farmers has been highlighted numerous environmental problems, affecting the productive agricultural system. This technological innovations reality and environmental obstacles, is also been experienced by cassava production in Paraíba rural area. Therefore, this study tried to assess the agroecosystems sustainability of cassava production (Manihot esculenta Crantz) of Paraíba Rural Mesoregion, using Sustainable Development Index (S³) method, and its graphical representation, the Biogram. The results showed sustainability differences between the agroecosystems of investigated municipalities, of which Araçagi showed stable levels of sustainability, Araruna and Bananeiras demonstrated unstable levels, and Puxinanã showed the most critical sustainably level. It was concluded that, even the agroecosystems of Araçagi municipality showing better levels of sustainability, when compared with other municipalities assessed, cassava production showed unsustainability situations regarding its technological innovation levels, average yield of cassava production, land in erosion process, water scarcity and lack of social participation.